Investigating gut permeability in neonatal calves with diarrhea: A case-control study - Luiza S. Zakia; Diego E. Gomez; Michael A. Steele; Peter D. Constable; Stephen J. LeBlanc; David L. Renaud (JDS Communications)
The objective of this case-control study was to assess gut permeability, measured through Cr-EDTA recovery, in healthy and diarrheic neonatal calves. The study was conducted at a commercial calf-rearing facility, where fecal consistency was monitored twice daily. Calves were categorized as diarrheic if they had runny or watery feces, whereas those with normal fecal consistency, neutrophil count, and physical exam findings were considered healthy controls. Gut permeability assessment (Cr-EDTA: 0.1 g/kg BW administered orally 2 h after milk feeding) and blood bacterial culture were performed 24 h after onset of diarrhea. Plasma Cr concentration was determined using inductively coupled plasma mass spectrometry. Wilcoxon signed-rank test and Kruskal-Wallis tests, followed by Dunn's post hoc test, were used to compare Cr concentrations between groups. The study included 12 healthy calves and 11 diarrheic calves, with 5 diarrheic calves having bacteremia. Diarrheic calves had greater median (interquartile range) plasma Cr concentrations than healthy calves at 2 h (1.76 [0.92–2.34] mg/L vs. 0.59 [0.48–1.19] mg/L) and 4 h (2.07 [1.57–2.51] mg/L vs. 0.92 [0.77–1.66] mg/L) postadministration, respectively. Both bacteremic and nonbacteremic calves with diarrhea had greater plasma Cr concentrations at 2 h compared with healthy calves (bacteremic: 1.96 [1.76–2.03] mg/L; nonbacteremic: 1.42 [0.78–2.34] mg/L), but there was no difference between bacteremic and nonbacteremic calves. At 4 h postadministration, both bacteremic (2.00 [1.67–2.07] mg/L) and nonbacteremic (2.45 [1.57–3.66] mg/L) diarrheic calves had greater plasma Cr concentrations than healthy calves, with no difference observed between bacteremic and nonbacteremic groups. This study suggests an association between diarrhea and increased gut permeability in neonatal calves. Further studies are required to compare gut permeability in a larger cohort of bacteremic and nonbacteremic diarrheic neonatal calves.